Isolated volar surgical approach for the treatment of perilunate and lunate dislocations - EROL, BÜLENT (SPRINGER HEIDELBERG, 2014)
Background: Volar and/or dorsal surgical approaches are used for surgical treatment of perilunate and lunate dislocations. There are no accepted approaches for treatment in the literature. We evaluated the functional results of isolated volar surgical approach for the treatment of perilunate and lunate dislocation injuries. Materials and Methods: 9 patients (6 male and 3 female patients average age 34.5 +/- 3.6 years) diagnosed with perilunate or lunate dislocations between January 2000 and January 2009 were involved in the study. The reduction was performed through isolated volar surgical approach and K-wire fixation, fracture stabilization with volar ligament repair was performed. Range of wrist joint motion, fracture healing, carpal stability, grip strength, return to work were evaluated and also direct radiographs were taken routinely at each control. The scapholunate interval and the scapholunate angle were evaluated radiographically. Evaluations of the clinical results were done using the DASH, VAS and Modified Mayo Wrist Scores. Results: The physical rehabilitation was started at 6th week, after the K-wires were removed. The average followup was 18.2 months (range 12-28 months). At the final followup, the average flexion extension arc was 105.0 +/- 9.6 degrees (74.6% of the other side), the average rotation arc was 138.8 +/- 7.8 degrees (81.5% of the other side) and the average radioulnar arc was 56.1 +/- 9.9 degrees (86.4% of the other side). The grip strength was 0.55 bar; 83.2% that the uninjured arm. According to the Mayo Modified Wrist score, the functional result was excellent in five patients and good in four and the average DASH score was 22.8. The scapholunate interval was 2.1 mm and scapholunate angle was 51 degrees. Conclusion: The clinical and radiological results of the isolated volar surgical approach were satisfactory. The dorsal approach was not needed for reduction of dislocations during operations. Our results showed that an isolated volar approach was adequate.
Keywords: Carpal instability; lunate dislocation; perilunate dislocation; volar surgical approach; PROXIMAL ROW CARPECTOMY; FRACTURE-DISLOCATIONS; DORSAL; REDUCTION; FIXATION; REPAIR; SCREW; WRIST